1778 N.Y. Laws 62 - (:unkn) unknown (My University, 1778)
Act of Apr. 3, 1778, ch. 33: Be it therefore enacted by the People of the state of New York represented in Senate and Assembly, and it is hereby enacted by the authority of the same. That every able bodied male person Indians and slaves excepted residing within this state from sixteen years of age to fifty (except such persons as are herein after excepted) shall immediately after the passing of this act tender himself to be enrolled as of the militia to the captain or in his absence the next commanding officer of the beat wherein he shall reside who shall inrol him accordingly and in case of delay, or neglect to make such tender as aforesaid the said captain or commanding officer shall cause such person to be enrolled and to be duly warned thereof . . . That every person so inrolled and notified shall within twenty days thereafter respectively furnish and provide himself at his own expence with a good musket or firelock fit for service . . .
Keywords: ARMED FORCES